Reduced gas accretion onto galaxies due to effects of external giant radio lobes - Yu Qiu; Renyue Cen (Proceedings of the National Academy of Sciences, 2025)
Suppression effects of giant radio lobes from supermassive black holes on gas accretion onto galaxies in the surrounding regions are quantified using cosmological magneto-hydrodynamic simulations. With an appropriate amount of radio jet energy injected into the intergalactic medium following the formation peak of supermassive black holes at redshift two, we find that galaxies in the greater neighborhood of the jet-launching massive galaxies subsequently experience a significant reduction in the amount of accreted gas. The distribution of the resulting magnetic field in the intergalactic medium is highly inhomogeneous, due to the highly biased nature of the most massive supermassive black holes. In regions with magnetic field strength B > 10 − 2 μ G, the baryon fraction is on average reduced by 17%, 14%, and 12%, respectively, for halos of mass in the range of [ 10 11 , 10 12 ) M ⊙ , [ 10 12 , 10 13 ) M ⊙ , and [ 10 13 , 10 14 ) M ⊙ . A proper inclusion of this new, external, global, preventive feedback mechanism from active galactic nuclei (AGN) in the next generation of cosmological simulation may be necessary.